Dialectics and Jurisprudence: A case study on the Interplay of Usūl al-Fiqh and Munāẓara in Nūr-al-Anwār - Md Yousef Kamal (22590461) (2025)
This conference contribution was presented by Md Yousef Kamal, Darul Huda Islamic University, India. (Qatar International Conference on Debate and Dialogue. An Initiative of QatarDebate 2025). While recent academic efforts have begun to explore the dialectical perspectives within Islamic jurisprudence, the Ḥanafī corpus, particularly Indian intellectual thought, has remained underexplored. This paper aims to illuminate the significance of such Indian texts by analyzing Mullā Jīwan’s Nūr-al-Anwār, focusing on its argumentation techniques, the discussion of wujūh fāsidah (invalid reasoning), and the confluence of methodology in inductive and deductive reasoning. Additionally, the paper will examine how Nūr-al-Anwār integrates these approaches within the framework of 18th-century Munāẓara and Jadal texts, highlighting their contribution to the evolution of Islamic dialectical theory. Other Information Conference information: The 2nd International Conference on Debate & Dialogue : An Initiative of QatarDebate (19 - 20 May 2025, Qatar National Conventions Center - QNCC, Doha - Qatar) License: https://creativecommons.org/licenses/by/4.0/ See the conference information on the organizer's website: https://qatardebate.org/programs/academic-programs/2nd-icdd/